داء الكيسات المائية في الكبد والرئة - القاضي سلمان; حاج قاسم فؤاد; محمــد محمـد (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 60 مريضاً، قبلوا، وعولجوا في قسم الجراحة في مشفى الأسد الجامعي باللاذقية، 33 أنثى (55%) و27 ذكراً (45%). تراوحت أعمار المرضى بين (18-70سنة). توزعت الإصابات كما يلي: الكبد 48 مريضاً (80%)، الرئة 14مريضاً(23.3%)، إصابة أكثر من عضو 12 مريض (20%)، أغلب إصابات الكبد وجدت في الفص الأيمن (71.9%)، وأغلب إصابات الرئة، وجدت في الفص السفلي الأيمن (57.14%). معظم الكيسات المائية كانت عرضية (90%)، واكتشفت حوالي(10%) من الحالات صدفة، وأغلب الأعراض لم تكن نوعية لهذا المرض. أجري لجميع المرضى صورة صدر بسيطة، وتصوير بالأمواج فوق الصوتية للبطن، وأجري لـ ( 42) مريضاً طبقي محوري للصدر والبطن, وكان مشخصاً في أغلب الحالات، وأجري تفاعل الأضداد لـ (40) مريضاً، وكان إيجابياً في (80%) من الحالات. عولج جميع المرضى جراحياً، وأتبعت الجراحة بعلاج دوائي (albendazole)، تراوحت نسبة المضاعفات بين(10 – 15%)، أهمها الناسور الصفراوي في الكبد, والناسور القصبي في الرئة, وأخطرها النزف. The study included 60 patients who were admitted to and treated in the Department of Surgery at Al-assad University Hospital, Lattakia: 33 females (55%) and 27 males (45%) between 18 and 70 years old. This disease was located in liver (48 cases) 80%, in lung (14cases) 23.3 %, and in many organs at the same time (12 cases) 20%. Most cases in liver were located in the right lobe (71.9%), and most cases of lung were located in the lower right lobe (57.14%). Most cysts were symptomatic (90%) of cases and asymptomatic in (10%) of cases and most symptoms were non specific. CXR and echo of abdomen was done for all patients, and CT of chest and abdomen was done for 42 patients; and it was diagnostic in most cases. Antigen reaction was done for 40 patients, and it was positive in (80%) of cases. All patients were treated surgically, followed with medical treatment (Albendazole). Complications rates were between 10 and 15 %. The most important complication was biliary fistula in liver and broncho-fistula in lung. Bleeding was the most dangerous complication.